2016
DOI: 10.2147/nss.s76706
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of sleep disturbances in Alzheimer's disease: current and emerging strategies

Abstract: Sleep and circadian disorders in Alzheimer’s disease (AD) are more frequent than in the general population and appear early in the course of the disease. Quality of sleep and quality of life are parallel in these patients, and such disorders also represent a heavy burden for caregivers. Although alterations in melatonin and hypocretins (orexins) seem to play a key role in the origin of these disturbances, the etiology of these disorders is multifactorial, including many factors such as environment, behavior, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 183 publications
(189 reference statements)
1
75
0
14
Order By: Relevance
“…Furthermore, insomnia and symptoms of insomnia have been linked to comorbid medical diseases (Akbaraly et al., ) as well as neurological and mental disorders (Urrestarazu & Iriarte, ). Especially in patients suffering from depression, insomnia is highly prevalent and may be prodromal to depression and as well constitute an independent risk factor for the occurrence of depressive episodes (Baglioni et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, insomnia and symptoms of insomnia have been linked to comorbid medical diseases (Akbaraly et al., ) as well as neurological and mental disorders (Urrestarazu & Iriarte, ). Especially in patients suffering from depression, insomnia is highly prevalent and may be prodromal to depression and as well constitute an independent risk factor for the occurrence of depressive episodes (Baglioni et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, 44% of patients with dementia (PwD) suffer from sleeping disturbances 3. Sleeping problem is a very vital problem not only for the patient but also for the caregiver.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of melatonin itself on treating sleeping disorders in dementia needs further research. Additionally, the impact of cholinesterase inhibitors (donepezil, rivastigmine, and galantamine) seems limited 3. Likewise, it is also a common phenomenon to use sedative–hypnotics and second-generation antipsychotics in order to treat sleeping disorders in dementia 12.…”
Section: Introductionmentioning
confidence: 99%
“…noted that elevated Aβ may lead to the fragmentation of nonrapid eye movement sleep [24]. Moreover, they and others found that lack of nonrapid eye movement sleep can also lead to the elevation of Aβ aggregation [23,24]. Investigations have further observed that clearance of Aβ may be compromised when sleep is diminished [25].…”
Section: Everyday Life Variablesmentioning
confidence: 99%
“…Sleep disturbances are endemic among patients with dementia, and the magnitude of sleep pathology frequently parallels disease progression [23]. This association has recently been clarified with a potential mechanism when Mander et al noted that elevated Ab may lead to the fragmentation of nonrapid eye movement sleep [24].…”
Section: Sleepmentioning
confidence: 99%